The Aspergillus niger Major Allergen (Asp n 3) DNA-Specific Sequence Is a Reliable Marker to Identify Early Fungal Contamination and Postharvest Damage in Mangifera indica Fruit - Martínez, Jorge; Nevado, Ander; Suñén, Ester; Gabriel, Marta; Vélez-del-Burgo, Ainara; Sánchez, Patricia; Postigo, Idoia (Frontiers in Microbiology, 2021)
The aim of this work was to study the value of the main allergen Asp n 3 of Aspergillus niger as a molecular marker of allergenicity and pathogenicity with the potential to be used in the identification of A. niger as a contaminant and cause of spoilage of Mangifera indica. Real-time polymerase chain reaction (RT-PCR) was used for the amplification of Asp n 3 gene. Two pairs of primers were designed: one for the amplification of the entire sequence and another one for the amplification of the most conserved region of this peroxisomal protein. The presence of A. niger was demonstrated by the early detection of the allergenic protein Asp n 3 coding gene, which could be considered a species-specific marker. The use of primers designed based on the conserved region of the Asp n 3 encoding gene allowed us to identify the presence of the closely related fungal species Aspergillus fumigatus by detecting Asp n 3 homologous protein, which can be cross-reactive. The use of conserved segments of the Asp n 3 gene or its entire sequence allows us to detect phylogenetically closely related species within the Aspergilaceae family or to identify species-specific contaminating fungi.